КОМПОЗИЦІЯ ТА «БЕЗПРЕДМЕТНИЙ» ЖИВОПИС В СИСТЕМІ НЕТРАДИЦІЙНИХ ПІДХОДІВ ДО ТВОРЧОГО ПРОЦЕСУ (Педагогіка вищої та середньої школи, 2022)
In article the points of view on «pointless» painting as on one of aspects of abstract art and nonconventional approaches to creative process are analysed.